Increasing Interest and Social Studies Learning Outcomes Through YouTube Video Based Learning Media in Class IXB SMPN 1 Bandar Laksamana - Yora Fitriani; Fatmariza Fatmariza (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2024)
This research was motivated by the low social studies learning outcomes of Grade IXB SMPN 1 Bandar Laksamana students due to the lack of student interest in participating in the social studies learning process using unattractive learning media and for this reason, efforts need to be made to increase students' interest in learning social studies so that learning outcomes can increase. The type of research used was participant class action research. This research was conducted at SMPN 1 Bandar Laksamana, Api-api Village Village, Bandar Laksaman District, Bengkalis Regency, Riau Province. The research subjects were Class IXB Students of SMPN I Bandar Laksamana with a total of 25 students. This research was conducted in odd semesters starting in July. The research procedure consisted of four stages namely planning, action, observation, and reflection. Research flow adapted from Kemmis and Mc Taggart. Data collection techniques used were questionnaires, observations, tests, interviews, documentation, and field notes. The data analysis technique uses percentage analysis. The research results show that the interest and learning outcomes of class IX.B students of SMPN 1 Bandar Laksamana by implementing YouTube video-based learning media have increased from cycle I to cycle II. The observations showed that the student's interest in cycle I reached a strong 20%% and experienced an increase in cycle II to a very strong 60%. This increase means that there is an increase in the character of student discipline by using YouTube video-based learning media from the good to the very good category. The observations showed that the average student learning outcomes also increased, starting from cycle I at 55.6 and increasing in cycle II to 79. With this increase,